Direct Methanation of Biogas—Technical Challenges and Recent Progress - Calbry-Muzyka, Adelaide S.; Schildhauer, Tilman J. (Frontiers in Energy Research, 2020)
The direct methanation of biogas using hydrogen from electrolysis is a promising pathway for seasonal storage of renewables in the natural gas network. It offers particular advantages over the methanation of carbon dioxide separated from biogas, as it eliminates a costly and unnecessary carbon dioxide separation step. The key implementation challenges facing direct methanation of biogas are reviewed here: 1) treatment of biogas impurities; 2) competing reactor concepts for methanation; and 3) competing process concepts for final upgrading. For each of these three aspects, the state of the art is reviewed, focusing especially on results which have been validated at a high Technology Readiness Level (TRL) at recent long-duration demonstrations. The different technology solutions have advantages and disadvantages which may fit best to different technical and economic boundary conditions, which are discussed. As a final outlook, TRL 8 demo plants will be necessary to show the full potential of these systems, and to obtain consistent operation data to allow a cost comparison.